2011
DOI: 10.1089/acm.2010.0596
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports of Sarcoma Patients with Optimized Lectin-Oriented Mistletoe Extract Therapy

Abstract: It seems that this disease is beneficially influenced by optimized lectin-oriented ME therapy since patients with sarcoma may react especially well to the improved balance of natural immunological mechanisms. These case reports require further clinical studies with patients with sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…These data, in line with the clinical findings in early clinical trials (15,17,19), support the potential of this plant-derived recombinant lectin I as an anticancer agent, particularly with regard to its combined use with immune checkpoint inhibitors or chemotherapeutics, as postulated in case reports and clinical investigations (22,33). Nevertheless, further studies to validate the present findings and assess the detailed mechanisms and clinical efficacy of aviscumine are warranted.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These data, in line with the clinical findings in early clinical trials (15,17,19), support the potential of this plant-derived recombinant lectin I as an anticancer agent, particularly with regard to its combined use with immune checkpoint inhibitors or chemotherapeutics, as postulated in case reports and clinical investigations (22,33). Nevertheless, further studies to validate the present findings and assess the detailed mechanisms and clinical efficacy of aviscumine are warranted.…”
Section: Discussionsupporting
confidence: 85%
“…The measured changes in patient plasma cytokine levels (increased IL-1β, TNF-α and IFN-γ and decreased IL-6 and IL-10 levels) indicate the activation of NK and T cells (19). A very recent study revealed that lectin structures represent PAMPs and thereby activate the immune system via PRRs (21)(22)(23). By focusing on NK cells, the present study was able to demonstrate a reproducible stimulation of NK cell antitumor activity for a non-toxic concentration range of aviscumine (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that ML molecules functioning as ligands for pattern recognition receptors of innate immune system and they are docked to appropriate ganglioside molecules (CD75) of natural immune cells [15]. Thereby ML is capable of having a positive effect on the disturbed immune balance of tumor patients and case reports show some clinical benefits [16][17][18]. The active (sugar-binding) lectin content of commercially available IscadorR M special preparations is regularly measured by an optimized ELLA technique as published previously [9].…”
Section: Discussionmentioning
confidence: 99%
“…Mistletoe is grown on different host trees such apple, pine, oak, fur, maple, poplar, or hawthorn. 23 In Europe, mistletoe lectin has been widely used as a complementary cancer drug for various cancers, such as gliomas, 24 acute lymphoblastic leukemia, 25 breast cancer, 26 sarcoma, 27 and others. 28 However, there has been no study showing the anticancer activity of mistletoe alkali.…”
Section: Ge Effects Of Mistletoe Alkali On Human Osteosarcoma Cells (mentioning
confidence: 99%